Postinfectious Bronchiolitis Obliterans in Children - Linfang Wan; Zhonghong Wang (Canadian Respiratory Journal)
Bronchiolitis obliterans is a rare form of chronic obstructive lung disease, with postinfectious bronchiolitis obliterans being particularly prevalent in pediatric populations. The pathogenic investigations of pediatric postinfectious bronchiolitis obliterans predominantly center on adenovirus and Mycoplasma pneumoniae. Following the illness, children’s lung function is impacted to varying extents; however, a definitive diagnosis relies on lung biopsy, which is not conducive to early detection and timely intervention. Consequently, there remains a need for novel research methodologies. This article synthesizes the 2023 China Reformulation of the Expert Consensus on the Diagnosis and Treatment of Bronchiolitis Obliterans in Children along with recent studies, providing a comprehensive overview of early diagnosis, treatment modalities, and preventive strategies for postinfectious bronchiolitis obliterans in children. Additionally, it outlines future research directions aimed at enhancing pediatricians’ understanding of this complex disease.